PENGARUH ROMANTICISM, SELF EXPRESSION DAN HEDONIC PRODUCTS TERHADAP BRAND LOYALITY MELALUI BRAND LOVE SEBAGAI VARIABEL INTERVENING PADA PENGGUNA IPHONE DI PALANGKA RAYA - Grace Evelina Buji (Bajang Institute, 2023)
This study aims to see the influence of Romanticism, Self Expression, and Hedonic Products on Brand Loyalty through Brand Love as Intervening variable on iPhone users in Palangka Raya. This research is a quantitative research using descriptive quantitative approach. Analysis tool in this research is Smart PLS application. The research variables consist of Romanticsm (X1), Self Expression (X2), Hedonic Product (X3), Brand Loves (Y1) and Brand Loyalty (Y2) as mediation variables. The sample uses Yamane method with statistic probability method of 96 samples from all iphone users that is not yet known by the population. The results of research Romantcism, Self Expression and Hedonic Product directly have not been able to influence the variable Brand Love and Brand Loyality. But with the existence of mediator variables such as brand love indirectly Romanticism, Self Expression and Hedonic Product able to influence brand loyalty variable with Brand Love as Intervening variable. Overall the results of this study are able to explain that intervening plays an important role to be the liaison for other variables